Prevalence of Polycystic Ovary Syndrome and its Associated Risk Factors among Adolescent and Young Girls in Ahmedabad Region - Desai, N. A.; Tiwari, R. Y.; Patel, S. S. (Indian Journal of Pharmacy Practice)
Objective: The aim of the present study was to determine prevalence, etiology of PCOS and its association with various factors in school going girls in Ahmadabad region. Study design: A cross-sectional community based study was conducted among the school going girls in five schools of Ahmedabad Gujarat region selected by cluster sampling. A total of 881 school going girls of age 13-18 years were involved in study. PCOS was diagnosed based on Rotterdam criteria. The association of PCOS with various factors were assessed. Estimation of Insulin, testosterone and LH was carried out. SF12 questionnaire was used for determination of quality of life. Data analysis was performed using the SPSS 9.0 PC package. Result: Out of 881 girls, 119 (13.54%) girls were found to have PCOS, as defined by the Rotterdam criteria. The higher % of PCOS girls belong to upper socioeconomic class (45.37). The highest % of PCOS girls were found to have family history of diabetes mellitus (37.81). The significant correlation was found between life style factors and PCOS girls (p≤ 0.05). The levels of LH and testosterone were found to be statistically significant in PCOS girls. There is higher percentage of girls are having poor quality of life as compared to normal girls. Conclusion: Obesity, socioeconomic status, family history, insulin resistance are the risk factors associated with PCOS. Hirsutism, acne, dysmenorrhea and oligomenorrhea were most common phenotype observed in PCOS.
Keywords: Mass Index; Hirsutism; Hyperandrogenesim; Polycystic Ovarian Syndrome (PCOS); Rottedram criteria.